2020
DOI: 10.15567/mljekarstvo.2020.0201
|View full text |Cite
|
Sign up to set email alerts
|

Morfologija vimena, proizvodnja mlijeka i zdravlje mliječne žlijezde malih preživača

Abstract: In recent years there has been an increasing trend in research of sheep and goat udder morphology, not only from the view of its suitability for machine milking, but also in terms of milk yield and mammary gland health. More precisely, herds consisting of high-yielding sheep and goats as a result of long-term and one-sided selection to increase milk yield, have been characterised by distortion of the udder morphology caused by increasing the pressure of udder weight on its suspensory system. Along with the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It has been shown that udder and teat morphologies are very heritable [1] and have direct repercussion on machine milking ability in dairy cattle [2][3][4][5][6], in dairy ewes [7][8][9][10][11][12] and dairy goats [13][14][15][16]. It has been also demonstrated that improving udder morphology and milkability traits lead to a better udder health and longevity of several dairy species [6,[17][18][19]. However, little information is available on camels' milkability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that udder and teat morphologies are very heritable [1] and have direct repercussion on machine milking ability in dairy cattle [2][3][4][5][6], in dairy ewes [7][8][9][10][11][12] and dairy goats [13][14][15][16]. It has been also demonstrated that improving udder morphology and milkability traits lead to a better udder health and longevity of several dairy species [6,[17][18][19]. However, little information is available on camels' milkability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the relation between measurements and milk quality parameters regard ruminants and mostly goats (Vrdoljak et al 2020) and have shown that the udder size is correlated with some milk components.…”
Section: Resultsmentioning
confidence: 99%
“…Machine milking reduces the milking time and creates better working conditions for the farmers (Gelasakis et al 2012). The conformation of the udders and teats of dairy animals is an important indicator of the aptitude for mechanical milking (Vrdoljak et al 2020). It affects the efficiency of the milking and milkability, and thus the aptitude of an animal to give a regular, complete, and rapid milk secretion in response to an appropriate milking technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations